Relationship between menarche and psychosis onset in women with first episode of psychosis. Issue 5 (27th September 2014) - Rubio‐Abadal, Elena; Usall, Judith; Barajas, Anna; Carlson, Janina; Iniesta, Raquel; Huerta‐Ramos, Elena; Baños, Iris; Dolz, Montserrat; Sánchez, Bernardo; ,; Ochoa, Susana
Abstract: Aim: The aim of this study was to explore the relationship between age at menarche and age at first episode of psychosis, as well as clinical severity and outcome, in a population of women with first‐episode psychosis. Methods: Clinical and socio‐demographical data, age at menarche and at first‐episode psychosis, parental history of psychosis and cannabis‐use habits were obtained from 42 subjects with a first episode of psychosis. Positive and Negative Syndrome Scale, Clinical Global Impression, Global Assessment Function, Disability Assessment Schedule, Wechsler Adult Intelligence Scale and Wechsler Intelligence Scale for Children, European Quality of Life, and Lewis and Murray Obstetric Complication Scales were administered. Statistical analysis was performed by means of zero‐order correlations and Mann–Whitney U and Kruskal–Wallis tests using SPSS version 17.0. Results: We found no significant correlation between age at menarche and age at first‐episode psychosis, or with the clinical scores performed. We observed that subjects with earlier age at menarche had more parental history of psychosis. Conclusions: Our negative results do not support the theory of a possible protective role of oestrogen, which seems to be more complex than previously thought. We would suggest that further research is needed to investigate developmental influences of sex steroids on the onset of psychosis and potentially therapeutic benefits based upon oestrogen.